Can The Performance of Millennial Employees Based on Emotional Intelligence Can Be Mediated By Work Life Balance ? (Study of Jabodetabek Employees) - Dellia Mila Vernia (Madani: Jurnal Ilmiah Multidisiplin, 2022)
In the midst of a global pandemic that has spread throughout the world at the beginning of 2020, it has had an impact on all lines of life, such as the health sector, education sector and the economic sector. The Covid 19 pandemic outbreak has completely restructured work organizations, this unexpected change has forced workers to adjust their work schedules so they can complete all responsibilities at home, to get maximum performance. Improving employee performance is an important requirement in achieving organizational goals and producing superior quality products and/or services. So that employees are expected to be able to balance work and home life, because during the Covid 19 pandemic, all work activities and personal life are centered at home. Therefore, there is a need for regularity between work tasks and housework. So, an employee must be able to create a work life balance. Respondents in this research were 200 employees who filled out a questionnaire via survey using the SEM PLS method. The results of the research state that emotional intelligence has a significant effect on work life balance, emotional intelligence has a significant effect on performance, work life balance has a significant effect on performance, and emotional intelligence has a significant effect on performance mediated by work life balance.